Screening of 18 Mediterranean plant species for volatile organic compound emissions - Owen, S; Boissard, C; Street, R A; Duckham, S C; Csiky, O; Hewitt, C N (Atmospheric Environment, 1997)
Eighteen tree and shrub species were screened for emissions of isoprene and other volatile organic compounds (VOCs) at three locations at Castelporziano (Italy) using a bag-enclosure sampling method followed by GC analysis. Thirty emitted compounds were identified. Temperature sensitivity of emissions of monoterpenes varied between species. Strong temperature dependencies were found for isoprene emissions. For monoterpene-emitting plant species with greatest ground cover in the dunes and macchia habitats, α-pinene, β-pinene and sabinene appeared to be the most frequently and abundantly emitted compounds. Isoprene was the major emission from the shrub species screened in the forest. Emissions from four dominant plant species were scaled up to estimate total fluxes from the dunes and macchia over a daytime period. Species with greatest biomass but low emission rates made a substantial contribution to total emissions.
Keywords: Arbutus unedo; Biogenic emissions; branch enclosure; Chrysanthemum praecox; cistus incanus; Cistus salvifolius; Cytisus sp.; Dittrichia sp.; Erica arborea; Erica multiflora; Helichrysum stoechas; isoprene; Juniperus oxycedrus; Juniperus phoenicea; Monoterpene; myrtus communis; Phillyrea angustifolia; Pinus pinea; Quercus cerris; Quercus ilex; Rubus fruticosus; Spartium junceum; VOCs

Seasonal water potential changes and proline accumulation in Mediterranean shrubland species - Lansac, A R; ZABALLOS, J P; Martin, A (Plant Ecology, 1994)
We studied the water relations of 6 shrub and 3 tree species typical of the mediterranean climate region of central Spain to identify differential responses to water stress between and within species, and to determine if free proline concentration in leaves could be used as a water stress indicator. Predawn and midday water potentials (ffdw) on a seasonal basis, relative water content (RWC), leaf mass per area, foliar nitrogen and free proline concentrations were measured. The lowest water potentials were observed at the end of the summer, with recovery to higher water potentials in the fall and winter seasons. Species differed regarding the annual qdw fluctuation. Thymus zygis, Halimium viscosum, Genista hirsuta and Juniperus oxycedrus exhibited the most negative midday and predawn ~ w (both less than -6 MPa) with a large magnitude of response to changing conditions in soil moisture of the upper horizon of the soil. Lavandula pedunculata and Cistus ladanifer showed a moderate response. Quercus rotundifolia, Quercus faginea and Retama sphaerocarpa showed a modest response. The ~ w of different size individuals of Quercus rotundifolia and Cistus ladanifer were compared. The annual fflw fluctuation was greater in small individuals as compared to large individuals. In every species, there was an increase in proline concentration of bulk leaf tissues when predawn kVw dropped below -5 MPa. Small plants of Cistus ladanifer reached lower water potentials and also higher concentration of proline than bigger plants. Proline could possibly be used as a drought stress indicator in every species except Q. rotundifolia. It is suggested that in addition to water stress avoidance due to deep root systems, some mechanisms of water stress tolerance may operate among shrub and tree species of central Spain.
Keywords: Cistus ladanifer; Genista hirsuta; Halimium viscosum; Juniperus oxycedrus; Lavandula pedunculata; Leaf mass per area; nitrogen; Proline; Quercus faginea; Quercus rotundifolia; Relative water content; retama sphaerocarpa; Thymus zygis; water potential